Art and human nature xxiii - Musso, Carlos G.; Enz, Paula A. (Revista del Hospital Italiano de Buenos Aires, 2016)
Imagination and fantasy are psychic activities whose primary role is to generate images that allow concrete processes of perception, reflection, and foresight, and the acquisition of the concept of identity. Carl Jung ranks the value of imagination in the human psyche and delivers in his Red Book fantastic images that will be the raw material of his scientific theories
Keywords: imagination; Red Book; Jung